1998
DOI: 10.1136/gut.42.5.711
|View full text |Cite
|
Sign up to set email alerts
|

Is colonoscopic surveillance reducing colorectal cancer mortality in ulcerative colitis? A population based case control study

Abstract: (Gut 1998;42:711-714)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
118
0
12

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(134 citation statements)
references
References 29 publications
(10 reference statements)
3
118
0
12
Order By: Relevance
“…In their series, as in ours, CRC was detected at a significantly earlier stage in patients who had undergone colonoscopic surveillance. Karlen et al, (1998) identified a trend towards a protective effect of colonoscopic surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their series, as in ours, CRC was detected at a significantly earlier stage in patients who had undergone colonoscopic surveillance. Karlen et al, (1998) identified a trend towards a protective effect of colonoscopic surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…We feel that it is prudent to join the ulcerative colitis and Crohn's colitis data, because there is increasing evidence that the pathogenesis and natural behaviour of inflammation-associated dysplasia in ulcerative colitis and Crohn's disease do not differ, and the risk of CRC is increased in both (1,2). A recent systematic review (Collins et al, 2006) by the Cochrane collaboration detected only three papers (Lashner et al, 1990;Choi et al, 1993;Karlen et al, 1998) that properly addressed the question of surveillance effectiveness for patients with ulcerative colitis. Other surveillance studies lacked valid control groups (Rosenstock et al, 1985;Lofberg et al, 1990;Nugent et al, 1991;Jonsson et al, 1994;Friedman et al, 2001;Biasco et al, 2002;Hata et al, 2003) or were not designed to answer this question (Eaden et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, no prior studies have indicated improved survival among UC patients with CRC when compared to those with sporadic CRC, as Shaukat et al [14] suggested. Studies by Karlen et al [21] and Choi et al [22] determined that colonoscopic surveillance is associated with an improved CRC survival in patients with UC when compared to UC patients not undergoing colonoscopic surveillance. These studies did not compare CRC survival in UC patients versus patients in the general population.…”
mentioning
confidence: 99%
“…These studies did not compare CRC survival in UC patients versus patients in the general population. As discussed above, these studies [21,22] along with a study by Lashner et al [23] were included in a Cochrane Collaboration analysis [19] that found no survival benefit in UC-CRC patients who underwent colonoscopic surveillance versus those who did not. Second, Shaukat et al assessed only 3-year CRC survival, whereas previous studies reported 5-year survival.…”
mentioning
confidence: 99%